Z-7=1+2Z

Simple and best practice solution for Z-7=1+2Z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Z-7=1+2Z equation:


Simplifying
Z + -7 = 1 + 2Z

Reorder the terms:
-7 + Z = 1 + 2Z

Solving
-7 + Z = 1 + 2Z

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '-2Z' to each side of the equation.
-7 + Z + -2Z = 1 + 2Z + -2Z

Combine like terms: Z + -2Z = -1Z
-7 + -1Z = 1 + 2Z + -2Z

Combine like terms: 2Z + -2Z = 0
-7 + -1Z = 1 + 0
-7 + -1Z = 1

Add '7' to each side of the equation.
-7 + 7 + -1Z = 1 + 7

Combine like terms: -7 + 7 = 0
0 + -1Z = 1 + 7
-1Z = 1 + 7

Combine like terms: 1 + 7 = 8
-1Z = 8

Divide each side by '-1'.
Z = -8

Simplifying
Z = -8

See similar equations:

| 6t=-21 | | 2Y+9=10Y | | 6x+9=rx+t | | x(90-x)=18 | | -22.5=7k-5.5k | | x+60-y-10=180 | | 3=x/-3-1 | | 2*(7/4)^2-7(7/4)-4 | | 15=7x-5(2x+3) | | 39=3(x+2) | | -3n-4+2n=-27 | | 29+12x=173 | | 198=-6(-6-3) | | 12x-20=-4x-16 | | 8k+12=52 | | -7x-28=-98 | | (2x-6)(2x-3)=0 | | 157*=2 | | log[3](2x+1)=2 | | 2xy^2-6x-3y=0 | | 12m^3-6m^2+3m= | | 3x=sqr(6) | | 3x=sqrt(6) | | 30=223/x | | -7x-11=16-8x | | Y^2=6y-9 | | 6(2x+1)=1 | | 18a^2b+27ab^2= | | -140=-5x+5(3x-16) | | 10-x=3x+24 | | 1x+1=2x-8 | | x^2-0.00469x+0.0002345=0 |

Equations solver categories